1804 Ind. Acts 108, A Law Entitled a Law Respecting Slaves, § 4 - (:unkn) unknown (General Publisher, 1804)
Prohibited a “slave or mulatto” from carrying or possessing a gun, powder, shot, club or other weapon and ammunition.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES